MAKTABGACHA YOSHDAGI BOLALARDA O‘YIN FAOLIYATI BOLA TARBIYASINING KAMOLOTI SIFATIDA - Usarova Muborak Xabibulla qizi; Narxolova Farangiz Umidjon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
The influence of play activities on the development of a child's personality and speech. The role and essence of play in the development of children of kindergarten age, games related to age groups. The importance of speech during play activities is discussed.